Does the treatment of proton pump inhibitors reduce dysplasia or adenocarcinoma development in Barrett’s esophagus? - Akın, Hakan; Aydın, Yücel (Turkish Journal of Gastroenterology, 2017)
Abstract Besides reducing the reflux symptoms, the benefit of proton pump inhibitors (PPI) in the treatment of Barrett's esophagus (BE) is not exactly known. The data in the literature show that although the PPI treatment does not reduce the Barrett's segment length, it can reduce dysplasia or the development of early-stage adenocarcinoma (odds ratio (OR): 0.46). Therefore, treatments with PPI may be considered in patients with a diagnosis of BE and at a high risk of adenocarcinoma, even though they are not symptomatic. Cite this article as: Akın H, Aydın Y. Does the treatment of proton pump inhibitors reduce dysplasia or adenocarcinoma development in Barrett's esophagus? Turk J Gastroenterol 2017;28(Suppl 1); S31-S32 Full Text Turkish